Fatty acid composition of the aerial parts of Urtica dioica (stinging nettle) L. (Urticaceae) - Bagci, E (Kluwer Academic/Plenum Publ, 2002)
[Abstract Not Available]
3rd IUPAC International Conference on Biodiversity -- NOV 03-08, 2001 -- ANTALYA, TURKEY